The renal cell cancer database Sweden (RCCBaSe) – a new register-based resource for renal cell carcinoma research. (3rd May 2020) - Landberg, Anna; Lindblad, Per; Harmenberg, Ulrika; Lundstam, Sven; Ljungberg, Börje; Thorstenson, Andreas; Sundqvist, Pernilla
Abstract: Introduction: In 2005, the National Swedish Kidney Cancer Register (NSKCR) was set up to collect data on newly diagnosed patients with renal cell carcinoma (RCC). In 2015, the NSKCR was linked to a number of national healthcare and demographic registers to construct the Renal Cell Cancer Database Sweden (RCCBaSe). The aim was to facilitate research on trends in incidence, effects of treatment and survival, with detailed data on tumour characteristics, treatment, pharmaceutical prescriptions, socioeconomic factors and comorbidity. Material and methods: All patients registered in the NSKCR between 2005 and 2014 were included. For each case, ten controls and first-degree relatives for cases and controls were identified. The RCCBaSe was created linking all cases, controls and first-degree relatives to a number of national registers with information on co-morbidity, socioeconomic factors and pharmaceutical prescriptions. Results: Between 2005 and 2014, a total of 9, 416 patients with RCC were reported to the NSKCR. 94, 159 controls and a total cohort of 575, 007 individuals including cases, controls and first-degree relatives were identified. Linkage to the Swedish cancer register resulted in 106, 772 matches. When linked to the National patient register, 432, 677 out-patient and 471, 359 in-patient matches were generated. When linked to the Swedish renal registry 1, 778 matches were generated. Linkage to the Prescribed drug register resulted in 448, 084 matches and linkage to the The Longitudinal integration database for health insurance and labour market studies database resulted in 450, 017 matches. Conclusion: By linking the NSKCR to several Swedish national databases, a unique database for RCC research has been created.